BDNF-Live-Exon-Visualization (BLEV) Allows Differential Detection of BDNF Transcripts in vitro and in vivo - Singer, Wibke; Manthey, Marie; Panford-Walsh, Rama; Matt, Lucas; Geisler, Hyun-Soon; Passeri, Eleonora; Baj, Gabriele; Tongiorgi, Enrico; Leal, Graciano; Duarte, Carlos B.; Salazar, Ivan L.; Eckert, Philipp; et al. (Frontiers in Molecular Neuroscience, 2018)
Bdnf exon-IV and exon-VI transcripts are driven by neuronal activity and are involved in pathologies related to sleep, fear or memory disorders. However, how their differential transcription translates activity changes into long-lasting network changes is elusive. Aiming to trace specifically the network controlled by exon-IV and -VI derived BDNF during activity-dependent plasticity changes, we generated a transgenic reporter mouse for BDNF-live-exon-visualization (BLEV), in which expression of Bdnf exon IV and-VI can be visualized by co-expression of CFP and YFP. CFP and YFP expression was differentially activated and targeted in cell lines, primary cultures and BLEV reporter mice without interfering with BDNF protein synthesis. CFP and YFP expression, moreover, overlapped with BDNF protein expression in defined hippocampal neuronal, glial and vascular locations in vivo. So far, activity-dependent BDNF cannot be explicitly monitored independent of basal BDNF levels. The BLEV reporter mouse therefore provides a new model, which can be used to test whether stimulus-induced activity-dependent changes in BDNF expression are instrumental for long-lasting plasticity modifications.